Cultural awareness through linguicism? Questioning the roles of native English speakers in Bogota, Colombia. (4th March 2019) - Khan, Cristine
ABSTRACT: Through recent educational initiatives that incorporate native English speakers (NESs) in achieving English proficiency, Colombia has seen an increase in NESs working as teachers or teaching assistants. This interpretive study uses qualitative methods to understand how NESs stimulate intercultural exchanges and awareness between Colombians and English-speaking foreigners; it looks specifically at private and public universities (formal spaces), and cafe-bars where language exchanges occur weekly (informal spaces) throughout Bogotá, Colombia. It finds that, essentialized ideas of both Anglophone and Latino cultures, dominant in such spaces, result in the promotion of stereotypes, exotification, and the privileging of NESs from specific countries and phenotypes over others by both NESs and Colombian language learners (CLLs). This study relates linguicism, or linguistic discrimination, as a factor that inhibits the potential for cultural awareness promoted through the use of NESs. The construction of an idealized, white NES delegitimizes non-Western Anglophone contexts, and upholds hegemonic standards of American and British English and cultures taught within English learning spaces. This places non-native English speakers and teachers in subaltern positions. Still, based on participant observations and interviews, it is evident that with intercultural training, NESs can assist in debunking preconceived, normative ideas about the English-speaking world.